Dealcoholisation of standard solutions by reverse osmosis and diafiltration - Jastřembská, Karolína; Jiránková, Hana; Mikulášek, Petr (My University, 2017)
One of the physical methods of beer dealcoholisation – reverse osmosis was chosen and studied. Four standard solutions were suggested for further research. These standard solutions contained basic substances of beer: water, ethanol and glucose. The effect of the substances added to the solution, and influence of retentate flow on the permeate flux were studied. The results of initial experiments were taken as the basis for further diafiltration process, where significant reduction of the ethanol concentration in the retentate was expected. Experimental results were compared with values calculated from mathematical model found in the cited literature.
Dealkoholizace modelových roztoků pomocí reverzní osmózy a diafiltrace
Keywords: Dealcoholisation; Standard solutions; Membrane processes; Reverse osmosis; Beer; Dealkoholizace; modelové roztoky; membránové procesy; reverzní osmóza; pivo